Adult Education-Related Graduate Degrees: Insights on the Challenges and Benefits of Online Programming - Dr. Mattyna Leevore Stephens; Dr. Joellen Coryell; Cindy Pena (Adult Education Research Conference, 2017)
The qualitative study sought to explore the perspectives of faculty in developing and teaching on-line adult education courses in a master’s program. The Four Frame Model framed the research.
Keywords: online adult education graduate programs; online instruction; teaching and learning online.